2014
DOI: 10.1177/1535370214538589
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and metabolism of tissue-engineered skeletal muscle

Abstract: Skeletal muscle is a major target for tissue engineering, given its relative size in the body, fraction of cardiac output that passes through muscle beds, as well as its key role in energy metabolism and diabetes, and the need for therapies for muscle diseases such as muscular dystrophy and sarcopenia. To date, most studies with tissue-engineered skeletal muscle have utilized murine and rat cell sources. On the other hand, successful engineering of functional human muscle would enable different applications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 124 publications
(236 reference statements)
6
54
0
Order By: Relevance
“…Exogenous biophysical and biochemical stimulations are traditionally applied to mimic natural environmental cues and encourage further cellular growth and have been reviewed in detail elsewhere [71, 72]. Mechanical stimulation, in the form of progressive or cyclic stretch to mimic growth [73] and exercise [74, 75] respectively, has been proven to enhance alignment [73, 75], fusion [73, 75], myofiber hypertrophy [62], and force generation [74, 75] in engineered constructs.…”
Section: Engineering Functional Muscle Constructsmentioning
confidence: 99%
“…Exogenous biophysical and biochemical stimulations are traditionally applied to mimic natural environmental cues and encourage further cellular growth and have been reviewed in detail elsewhere [71, 72]. Mechanical stimulation, in the form of progressive or cyclic stretch to mimic growth [73] and exercise [74, 75] respectively, has been proven to enhance alignment [73, 75], fusion [73, 75], myofiber hypertrophy [62], and force generation [74, 75] in engineered constructs.…”
Section: Engineering Functional Muscle Constructsmentioning
confidence: 99%
“…When stimulated electrically or chemically, the engineered skeletal muscle responded much like a normal tissue in terms of releasing calcium ions followed by twitching. The average tetanus force generated by the engineered muscles was far lower than that reported for adult muscle, but was similar to the values measured in foetal human muscle [154,155]. Testing three classes of pharmaceutical drugs revealed that they had similar effects on the engineered muscle as on normal muscle tissue under clinical settings.…”
Section: Drug Screeningmentioning
confidence: 79%
“…The previous MPS thematic issue in EBM published manuscripts highlighting early progress from both of these efforts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] It was recognized that MPS might help close the hermeneutic circle of biology, which describes how it is impossible to understand the whole (the compete organism) without understanding the parts (the genome, proteome, metabolome, etc. ), and that understanding the parts requires an understanding of the whole.…”
Section: The Entry Of Mps Onto the Biomedical Scenementioning
confidence: 99%
“…A much more comprehensive battery of techniques is already in regular use in the pharmaceutical industry, including genomics, transcriptomics, and proteomics. In recent MPS studies, we are seeing functional measurements such as contractility, calcium signaling, and electrophysiological responses of cardiac and skeletal muscle, 37,[69][70][71][72][73][74][75] electrical resistance and molecular permeability of barriers, [76][77][78][79][80][81][82] and metabolomic responses to inflammatory challenges. 78 In this issue, the Parker group uses a variety of measures, including gene expression profiling, to quantify factors that affect maturation of neonatal rat cardiomyocytes into a more mature phenotype.…”
Section: Fitting Into the "Grand Scheme"mentioning
confidence: 99%